Evaluation of Surface Melt on the Greenland Ice Sheet Using SMAP L-Band Microwave Radiometry - Mohammad Mousavi (IEEE, 2021)
Monitoring melt extent and timing on the Greenland ice sheet is important for tracking the ice sheet's mass and energy balance as well as the global and Arctic climate variability and change. In this study, we use L-band (1.4 GHz) brightness temperature observations collected by NASA's soil moisture active passive (SMAP) mission to investigate the extent, duration, and intensity of melt events on the Greenland ice sheet from 2015 to 2021. SMAP provides nearly all-weather surface monitoring over all of Greenland twice daily with morning and evening overpasses at approximately 40-km spatial resolution. We applied empirical threshold and geophysical-model-based algorithms using horizontally and vertically polarized microwave brightness temperature differences to quantify both the intensity and extent of surface melting. Analysis of the melt seasons shows that Greenland experienced unusually strong melt events at the end of July 2019 and on August 14, 2021, which extended the melt area across much of the dry snow zone over a period of one and two days, respectively. In situ temperatures measured at Greenland's Summit station confirm the above freezing temperatures during these extreme events.